Short-term Influence of Glyphosate on Microorganisms in Backyard Compost - Kwiatkowska, Klaudia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The composting process is a natural method of waste disposal. Decomposition of organic matter occur with the participation of various groups of microorganisms. Using glyphosate-based herbicides aims to reduce agricultural losses. Biodegradation of glyphosate in soil is obtain with bacteria and fungi and may affect their functioning. The purpose of this study was evaluating the effects of glyphosate on bacterial diversity during composting and to monitor potential changes in community structure and species abundance.
Keywords: composts; microorganisms; glyphosate; herbicide; soil